Investigation of Different Reinforced Composite Materials for Surface Roughness and Capacity of Being Drilled - Pihtili, Hasim; Canpolat, Nusret (Sage Publications Ltd, 2009)
In this study, drilling performance and cutting parameters with holes having different qualities, drill kinds, and drill diameters were examined in different composite materials. HSS, TIN, and carbide drills with 5, 10, and 15 mm diameter were used in drilling processes. Experiments were conducted with dry drilling at different cutting speeds of 125, 250, and 315 rpm and progresses of 0.056, 0112, and 0.16 mm/rev. Different kinds of composites with different reinforced composites were used as materials. As a result of the drilling operations, it is found that as rotation and progress speed increases, surface roughness on the processed surface increases as well. Better results in terms of surface roughness were obtained with small-scaled drills. All obtained values were conveyed into the graphics as well as the tables. Furthermore, photos of all samples under electron microscope were taken and the condition of the photos were examined for surface roughness intensity.
Keywords: reinforced composite materials; drilling; roughness